Evaluasi Proses Bisnis Menggunakan Metode Quality Evaluation Framework (QEF) (Studi Pada Bagian E-Government Dinas Komunikasi dan Informatika Kabupaten Gresik) - Fajar Ubaidillah Ahmad; Buce Trias Hanggara; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Communication and Informatics Office of Gresik Regency is the office of the communication and informatics office of Gresik Regency, East Java province. The Office of Communication and Information of Gresik Regency has the task of organizing government affairs in the field of communication and informatics for the Gresik Regency area, East Java. The business process at the Gresik regency communication and information office is supported by a Standard Operating Procedure (SOP) which must be carried out by certain parties from beginning to end relating to existing work programs. There is a business process at the Gresik Regency Communication and Information Office that has not been going well. In the task "Development and Development of E-Government Applications and Data" which is carried out from the beginning to the end of the limit in a long time, namely for more than ten days. Whereas in the SOP document the process should be shorter, that is, within seven days. The process is not subject to this fee beyond the time specified in the SOP document, so it can hinder other processes that are mutually sustainable. The evaluation process must be carried out using the Quality Evaluation Framework (QEF) and Root Cause Analysis methods. The first step is to identify business processes with problems, then model the business processes using the Business Process Model and Notation (BPMN). Next, determine the quality factor along with the calculation target and perform calculations according to the equation in the QEF method. Then perform the ability on quality factors that are not in accordance with the company's targets. After that, analysis is carried out using Root Cause Analysis in order to find out the root of the problems that occur in the business process.